2008
DOI: 10.1148/radiol.2491071600
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Leiomyomas: MR Imaging–guided Focused Ultrasound Surgery—Imaging Predictors of Success

Abstract: Purpose:To retrospectively assess the magnetic resonance (MR) imaging predictors of success at reducing uterine leiomyoma volume and achieving patient symptom relief 12 months after MR imaging-guided focused ultrasound surgery. Materials and Methods:This single-center retrospective analysis of 71 symptomatic fibroids in 66 women was approved by the institutional review board and was HIPAA-compliant. Patients were treated with MR imaging-guided focused ultrasound surgery. The volume of treated fibroid and nonpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(86 citation statements)
references
References 23 publications
5
79
1
1
Order By: Relevance
“…100,101 Extracorporeal HIFU enables ablation of various sizes and shape of fibroid. Symptoms are reduced by more than 50% in terms of pain, [102][103][104] bulk-related and menstrual symptoms, comparable with the results of conventional surgery. 105 After HIFU, the ablated fibroid volume is decreased, and is related to the non-perfused volume of the tumour immediately after treatment.…”
Section: Fibroidssupporting
confidence: 60%
“…100,101 Extracorporeal HIFU enables ablation of various sizes and shape of fibroid. Symptoms are reduced by more than 50% in terms of pain, [102][103][104] bulk-related and menstrual symptoms, comparable with the results of conventional surgery. 105 After HIFU, the ablated fibroid volume is decreased, and is related to the non-perfused volume of the tumour immediately after treatment.…”
Section: Fibroidssupporting
confidence: 60%
“…A very recent study has determined that older patients (mean age 46) were more likely to be associated with long-term treatment success [30]. We and others [30,31] have also shown that fibroids of low SI on pretreatment T2-weighted MR images are more likely to decrease in size post-MRgFUS compared with more cellular fibroids of high SI on T2 WI.…”
Section: Clinical Outcome With Mrgfusmentioning
confidence: 67%
“…Lénárd et al (8) and Funaki et al (9) have observed that the NPV ratio of hyperintense uterine fibroids is reduced compared with that of hypointense and isointense fibroids; therefore, HIFU may not be an appropriate treatment method for hyperintense fibroids. However, the results of the present study indicated that the majority of hyperintense uterine fibroids may be eligible for HIFU ablation, based on the technical success of the present procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroids are defined as hyperintense if their pretreatment signal intensity appears to be equal to or greater than the surrounding myometrium under T2-weighted MRI. Previous studies (8,9) have observed that hyperintense fibroids exhibit a smaller average NPV and lower regression rates compared with isointense or hypointense fibroids following HIFU ablation. Therefore, hyperintense fibroids should be exempted from this procedure.…”
Section: Introductionmentioning
confidence: 88%